Analysis Of The Quality Of Public Services At The Office Of The Takalar District Population And Civil Registration Office - Niswaty, Risma; Rahyuni, Rahyuni; Aslinda, Andi (Universitas Negeri Makassar, 2023)
The implementation of regional government which was marked by the enactment of Law No. 32 of 2004 concerning Regional Government has had far-reaching consequences for the government agency for the analysis of the quality of public services at the Office of Population and Civil Registration of Takalar Regency. This research is a qualitative descriptive study that aims to determine the quality of public services at the Office of the Population and Civil Registration Office of Takalar Regency. Data collection techniques through observation, interviews, and documentation. The results of the study show that the analysis of the quality of public services at the office of the takalar district population and civil registration office seen from the Tangible dimension (physical evidence) has been implemented. The Reability dimension has been implemented, but there are still indicators that have not met people's expectations, namely regarding the expertise of employees in using assistive devices. The Responsiveness dimension has been implemented, but there are indicators that have not met the expectations of the community regarding the timeliness of employees in providing services. The Assurance dimension has been implemented according to the wishes of the community. The Empathy Dimension has been implemented. This study presents new, more detailed information by linking the latest theory compared to previous research regarding the quality of public services at the Population and Civil Registration Office of Takalar Regency so that it can be used as evaluation material for research loci to further improve the quality of their services